Preparation method of soft and hard composite anti-icing coating with low icing adhesion
By using a combination of modified epoxy resin and hard particles in the anti-ice coating, the problem of degradation of durability and hydrophobic properties of the anti-ice coating in the prior art is solved, and better anti-ice effect and Long-term stability.
Patent Information
- Application Number
- CN202411871224.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing hydrophobic anti-ice coating has gradually declined under long-term outdoor exposure, affecting the anti-ice coating effect and durability.
The preparation method of soft and hard composite low ice adhesion anti-ice coating is adopted. By introducing a combination of modified epoxy resin, hard particles and soft particles, the hardness, wear resistance and toughness of the coating are improved, and ice and snow are reduced. adhesion of the layer.
It significantly improves the anti-ice effect and long-term durability of the anti-ice coating, enhances the hydrophobicity, mechanical strength and anti-aging properties of the coating, and promotes the rapid fall of the ice.
Smart Images

Figure PMA3SKTJD64ULJL3IUSGICTSKI4WFUN5TJCBDH0S
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-icing coatings, and in particular to a method for preparing a soft-hard composite low-icing adhesion anti-icing coating. Background Art
[0002] Research on anti-icing coatings for power systems has received widespread attention in recent years and has made significant progress. In terms of hydrophobic coatings, researchers have used bionic design to imitate natural hydrophobic surfaces such as lotus leaves, used nanotechnology to construct microscopic rough structures, and combined with low surface energy materials to effectively reduce the adhesion between the ice layer and the coating. For example, nano-silica and fluororesin composite coatings showed excellent hydrophobicity and anti-icing properties under experimental conditions. At the same time, research on electrothermal coatings has also achieved remarkable results. By adding conductive fillers such as graphene and carbon nanotubes to the coating, heat can be generated to melt ice when power is turned on, thereby actively responding to the threat of icing.
[0003] However, the durability of the hydrophobic coating still needs to be further improved. Under long-term outdoor exposure, the hydrophobic properties of the coating will gradually decrease, which directly affects the anti-icing effect and long-term durability of the coating. In view of this, we propose a method for preparing a soft-hard composite low-icing adhesion anti-icing coating. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a soft-hard composite low ice adhesion anti-icing coating to solve the problems raised in the above background technology.
[0005] To achieve the above-mentioned object, the present invention provides a method for preparing a soft-hard composite low ice adhesion anti-icing coating, S1.1, weighing the following raw materials in parts by weight: 75-90 parts by weight of modified epoxy resin, 10-25 parts by weight of acrylic resin, 6-8 parts by weight of vinyl-terminated polydimethylsiloxane, 1-3 parts by weight of hydrogen-containing silicone oil, 0.5-1 parts by weight of platinum catalyst, 0.8-1.2 parts by weight of emulsifier, 5-10 parts by weight of coconut shell activated carbon, 11-13 parts by weight of octadecyltriethoxysilane, 0.4-0.8 parts by weight of dibutyltin dilaurate, 8-12 parts by weight of isophoronediamine, 7-9 parts by weight of polydimethylsiloxane and 1-3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:6-8, and adding 1-aminobenzotriazole; S1.2, preparing silicone rubber microspheres, i.e. soft particles, from vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil, platinum catalyst, emulsifier and deionized water; S1.3, preparing hard hydrophobic activated carbon particles, i.e. hard particles, from coconut shell activated carbon, octadecyltriethoxysilane, anhydrous ethanol and dibutyltin dilaurate; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300-400rpm at room temperature for 15-20min to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15-20min, add isophorone diamine, continue ultrasonic treatment for 2-3min, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 300-400rpm at room temperature for 10-15min, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3-5min to obtain a low ice adhesion coating.
[0006] The performance of the coating is improved by introducing a combination of hard and soft particles. The hard particles can enhance the hardness and wear resistance of the coating and effectively resist external friction and wear. At the same time, the soft particles can improve the toughness of the coating and reduce brittle fracture. The combination of the two can reduce the adhesion of ice and snow to the coating through a local stress concentration mechanism and promote the rapid shedding of the ice layer, thereby enhancing the anti-icing effect and long-term durability of the coating.
[0007] Preferably, the specific steps involved in S1.2 are: Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, stir at 2000-3000rpm for 20-30min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 50-60℃ for 2-3h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 1000-2000rpm for 3-5min, then wash with deionized water and anhydrous ethanol for 2-3 times respectively, and finally dry at 70-80℃ for 1-2h to obtain silicone rubber microspheres, i.e. soft particles.
[0008] Preferably, in S1.2, the mass ratio of the emulsifier to the deionized water in the emulsion is 1:100-200, and the particle size range of the silicone rubber microspheres is 3-7 μm.
[0009] Preferably, the specific steps involved in S1.3 are: The coconut shell activated carbon is dried in a vacuum drying oven at 100-120°C for 12-18h, then ground through a 250 mesh sieve, octadecyltriethoxysilane is dissolved in anhydrous ethanol to prepare a silane solution, and dibutyltin dilaurate is added, mixed and stirred evenly to obtain a hydrophobic modifier, the ground coconut shell activated carbon powder is mixed with the hydrophobic modifier, and after ultrasonic treatment for 50-60min, it is transferred to a three-necked flask, stirred and reacted in a water bath at 60-70°C for 6-8h, cooled and centrifuged after the reaction is completed, washed with anhydrous ethanol and deionized water for 2-3 times respectively, and finally vacuum dried at 60-80°C for 12-18h to obtain hard hydrophobic activated carbon particles, i.e. hard particles.
[0010] Preferably, in S1.3, the mass fraction of the silane solution is 1-3%, and the mass ratio of the ground coconut shell activated carbon powder to the hydrophobic modifier is 1:10-15.
[0011] Preferably, in S1.4, the amount of soft particles added is 1-10% of the total mass of the low ice adhesion coating.
[0012] Preferably, in S1.4, the amount of hard particles added is 1-8% of the total mass of the low ice adhesion coating.
[0013] Preferably, in S1.4, the steps of preparing the modified epoxy resin are specifically: Assemble a magnetic stirrer in a dry flask and install a condenser. First add dichloromethane into the flask, then add bisphenol A epoxy resin, start stirring, and after the epoxy resin is completely dissolved, add trifluoromethylphenethylamine and continue stirring. Heat the reaction mixture to 50-60°C. When the temperature stabilizes, add 1-aminobenzotriazole, keep stirring and react at this temperature for 1-2 hours to obtain a modified epoxy resin.
[0014] The amino group of o-trifluoromethylphenylethylamine can undergo nucleophilic addition reaction with the epoxy group in epoxy resin, opening the epoxy ring and forming a cross-linked network, which promotes the curing process of epoxy resin and forms a strong and durable three-dimensional polymer network. 3 ) has extremely low surface energy and good hydrophobicity, which can significantly reduce the surface energy of the material, enhance the waterproof performance of the coating, help reduce ice adhesion, and improve resistance to a variety of chemicals. Epoxy resin coatings containing trifluoromethyl also show better anti-fouling and self-cleaning properties, while providing better protection in harsh environments. The aromatic structure can give the material higher thermal stability; and the trifluoromethyl group helps to improve the material's high temperature resistance. In addition, the rigid aromatic skeleton can also increase the cross-linking density, thereby increasing the hardness and wear resistance of the material, so that the final epoxy resin material has better thermal stability and mechanical strength.
[0015] Due to the aromatic structure and the presence of trifluoromethyl group of o-trifluoromethylphenethylamine, its reaction activity is not high, so 1-aminobenzotriazole is added to improve the reaction activity of o-trifluoromethylphenethylamine. Since 1-aminobenzotriazole contains an amino group, which is a basic functional group, it can act as a proton acceptor to increase the nucleophilicity of the epoxy group, thereby accelerating the cross-linking reaction between the epoxy resin and the amine curing agent. In addition, the benzotriazole ring itself is relatively stable and is not prone to decomposition or rearrangement reactions. It has good ultraviolet absorption ability and can reduce degradation caused by ultraviolet rays. It can be used to improve the weather resistance and anti-aging properties of the material.
[0016] Preferably, the amount of 1-aminobenzotriazole added is 0.1-0.5% of the mass of the bisphenol A epoxy resin.
[0017] Preferably, the added amount of dichloromethane is 20-30% of the mass of the epoxy resin.
[0018] Compared with the prior art, the present invention has the following beneficial effects: In the preparation method of the soft-hard composite low ice adhesion anti-icing coating, o-trifluoromethylphenethylamine is used to improve the hydrophobicity of bisphenol A epoxy resin, which can reduce the contact area between water molecules and the surface, form larger water droplets and easily roll off, thereby reducing the formation of ice on the surface and reducing the ice adhesion. At the same time, the alkalinity of 1-aminobenzotriazole is used to improve the activity of o-trifluoromethylphenethylamine on the one hand, promote the reaction of o-trifluoromethylphenethylamine linking to bisphenol A epoxy resin, and on the other hand, the ultraviolet absorption capacity of the benzotriazole ring is used to improve the weather resistance and anti-aging properties of the material. In addition, a composite structure of hard particles and soft particles is introduced at the same time, and the hard particles are used to enhance the mechanical strength, and the soft particles are used to reduce brittleness and improve toughness. Under the synergistic effect, the mechanical properties of the material can be effectively improved, and a local stress concentration area can be formed on the surface of the material, which is helpful to guide the stress concentration when the ice layer is formed, and then promote the local cracking and shedding of the ice layer, effectively accelerating the shedding process of the ice. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] A method for preparing a soft-hard composite low ice adhesion anti-icing coating of the present invention: S1.1, weigh the following raw materials in parts by weight: 75-90 parts by weight of modified epoxy resin, 10-25 parts by weight of acrylic resin, 6-8 parts by weight of vinyl-terminated polydimethylsiloxane, 1-3 parts by weight of hydrogenated silicone oil, 0.5-1 parts by weight of platinum catalyst, 0.8-1.2 parts by weight of emulsifier, 5-10 parts by weight of coconut shell activated carbon, 11-13 parts by weight of octadecyltriethoxysilane, 0.4-0.8 parts by weight of dibutyltin dilaurate, 8-12 parts by weight of isophoronediamine, 7-9 parts by weight of polydimethylsiloxane and 1-3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:6-8, and adding 1-aminobenzotriazole; S1.2, vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst are added to a constant temperature reactor, and an emulsifier and deionized water are added to another beaker, and stirred at a speed of 2000-3000rpm for 20-30min to form an emulsion, and the emulsion is transferred to a constant temperature reactor, and reacted at 50-60℃ for 2-3h. Stirring is continued during the reaction. After the reaction is completed, the mixture is naturally cooled and centrifuged at a centrifugal speed of 1000-2000rpm for 3-5min, and then washed with deionized water and anhydrous ethanol for 2-3 times respectively, and finally dried at 70-80℃ for 1-2h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 12-18h, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder with the hydrophobic modifier, transfer it to a three-necked flask after ultrasonic treatment for 50-60min, stir and react in a water bath at 60-70°C for 6-8h, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 2-3 times respectively, and finally vacuum dry at 60-80°C for 12-18h to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300-400rpm at room temperature for 15-20min to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15-20min, add isophorone diamine, continue ultrasonic treatment for 2-3min, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 300-400rpm at room temperature for 10-15min, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3-5min to obtain a low ice adhesion coating.
[0021] Wherein, the emulsifier is Tween 80 emulsifier.
[0022] Embodiment 1: A method for preparing a soft-hard composite low ice adhesion anti-icing coating, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 90 parts by weight of modified epoxy resin, 25 parts by weight of acrylic resin, 8 parts by weight of vinyl-terminated polydimethylsiloxane, 3 parts by weight of hydrogenated silicone oil, 1 part by weight of platinum catalyst, 1.2 parts by weight of Tween 80 emulsifier, 10 parts by weight of coconut shell activated carbon, 13 parts by weight of octadecyltriethoxysilane, 0.8 parts by weight of dibutyltin dilaurate, 12 parts by weight of isophoronediamine, 9 parts by weight of polydimethylsiloxane and 3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:6, and adding 1-aminobenzotriazole; the addition amount of 1-aminobenzotriazole is 0.1% of the mass of bisphenol A epoxy resin; the addition amount of soft particles accounts for 5% of the total mass of the low ice adhesion coating; the addition amount of hard particles accounts for 3% of the total mass of the low ice adhesion coating; A magnetic stirrer is installed in a dry flask, and a condenser is installed. Dichloromethane is first added to the flask, and then bisphenol A epoxy resin is added. The amount of dichloromethane added is 30% of the mass of the epoxy resin. Stirring is started. After the epoxy resin is completely dissolved, o-trifluoromethylphenylethylamine is added. Stirring is continued. The reaction mixture is heated to 60° C. When the temperature is stable, 1-aminobenzotriazole is added. Stirring is maintained and the reaction is carried out at this temperature for 1 hour to obtain a modified epoxy resin. S1.2. Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, wherein the mass ratio of emulsifier to deionized water in the emulsion is 1:200, stir at 3000 rpm for 30 min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 60°C for 3 h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 2000 rpm for 5 min, then wash with deionized water and anhydrous ethanol for 3 times respectively, and finally dry at 80°C for 1 h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 18 hours, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution with a mass fraction of 2%, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder and the hydrophobic modifier in a mass ratio of 1:10, transfer to a three-necked flask after ultrasonic treatment for 60 minutes, stir and react in a water bath at 70°C for 8 hours, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 3 times respectively, and finally vacuum dry at 80°C for 18 hours to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300 rpm for 15 minutes at room temperature to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15 minutes, add isophorone diamine, continue ultrasonic treatment for 2-3 minutes, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 400 rpm for 10 minutes at room temperature, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3 minutes to obtain a low ice adhesion coating.
[0023] Embodiment 2: A method for preparing a soft-hard composite low ice adhesion anti-icing coating, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 90 parts by weight of modified epoxy resin, 25 parts by weight of acrylic resin, 8 parts by weight of vinyl-terminated polydimethylsiloxane, 3 parts by weight of hydrogenated silicone oil, 1 part by weight of platinum catalyst, 1.2 parts by weight of Tween 80 emulsifier, 10 parts by weight of coconut shell activated carbon, 13 parts by weight of octadecyltriethoxysilane, 0.8 parts by weight of dibutyltin dilaurate, 12 parts by weight of isophoronediamine, 9 parts by weight of polydimethylsiloxane and 3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and trifluoromethylphenylethylamine in a mass ratio of 50:7 and adding 1-aminobenzotriazole; the addition amount of 1-aminobenzotriazole is 0.3% of the mass of bisphenol A epoxy resin; the addition amount of soft particles accounts for 5% of the total mass of the low ice adhesion coating; the addition amount of hard particles accounts for 3% of the total mass of the low ice adhesion coating; A magnetic stirrer is installed in a dry flask, and a condenser is installed. Dichloromethane is first added to the flask, and then bisphenol A epoxy resin is added. The amount of dichloromethane added is 30% of the mass of the epoxy resin. Stirring is started. After the epoxy resin is completely dissolved, o-trifluoromethylphenylethylamine is added. Stirring is continued. The reaction mixture is heated to 60° C. When the temperature is stable, 1-aminobenzotriazole is added. Stirring is maintained and the reaction is carried out at this temperature for 1 hour to obtain a modified epoxy resin. S1.2. Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, wherein the mass ratio of emulsifier to deionized water in the emulsion is 1:200, stir at 3000 rpm for 30 min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 60°C for 3 h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 2000 rpm for 5 min, then wash with deionized water and anhydrous ethanol for 3 times respectively, and finally dry at 80°C for 1 h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 18 hours, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution with a mass fraction of 2%, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder and the hydrophobic modifier in a mass ratio of 1:10, transfer to a three-necked flask after ultrasonic treatment for 60 minutes, stir and react in a water bath at 70°C for 8 hours, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 3 times respectively, and finally vacuum dry at 80°C for 18 hours to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300 rpm for 15 minutes at room temperature to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15 minutes, add isophorone diamine, continue ultrasonic treatment for 2-3 minutes, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 400 rpm for 10 minutes at room temperature, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3 minutes to obtain a low ice adhesion coating.
[0024] Embodiment 3: A method for preparing a soft-hard composite low ice adhesion anti-icing coating, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 90 parts by weight of modified epoxy resin, 25 parts by weight of acrylic resin, 8 parts by weight of vinyl-terminated polydimethylsiloxane, 3 parts by weight of hydrogenated silicone oil, 1 part by weight of platinum catalyst, 1.2 parts by weight of Tween 80 emulsifier, 10 parts by weight of coconut shell activated carbon, 13 parts by weight of octadecyltriethoxysilane, 0.8 parts by weight of dibutyltin dilaurate, 12 parts by weight of isophoronediamine, 9 parts by weight of polydimethylsiloxane and 3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:8, and adding 1-aminobenzotriazole; the addition amount of 1-aminobenzotriazole is 0.5% of the mass of bisphenol A epoxy resin; the addition amount of soft particles accounts for 5% of the total mass of the low ice adhesion coating; the addition amount of hard particles accounts for 3% of the total mass of the low ice adhesion coating; A magnetic stirrer is installed in a dry flask, and a condenser is installed. Dichloromethane is first added to the flask, and then bisphenol A epoxy resin is added. The amount of dichloromethane added is 30% of the mass of the epoxy resin. Stirring is started. After the epoxy resin is completely dissolved, o-trifluoromethylphenylethylamine is added. Stirring is continued. The reaction mixture is heated to 60° C. When the temperature is stable, 1-aminobenzotriazole is added. Stirring is maintained and the reaction is carried out at this temperature for 1 hour to obtain a modified epoxy resin. S1.2. Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, wherein the mass ratio of emulsifier to deionized water in the emulsion is 1:200, stir at 3000 rpm for 30 min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 60°C for 3 h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 2000 rpm for 5 min, then wash with deionized water and anhydrous ethanol for 3 times respectively, and finally dry at 80°C for 1 h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 18 hours, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution with a mass fraction of 2%, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder and the hydrophobic modifier in a mass ratio of 1:10, transfer to a three-necked flask after ultrasonic treatment for 60 minutes, stir and react in a water bath at 70°C for 8 hours, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 3 times respectively, and finally vacuum dry at 80°C for 18 hours to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300 rpm for 15 minutes at room temperature to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15 minutes, add isophorone diamine, continue ultrasonic treatment for 2-3 minutes, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 400 rpm for 10 minutes at room temperature, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3 minutes to obtain a low ice adhesion coating.
[0025] Embodiment 4: A method for preparing a soft-hard composite low ice adhesion anti-icing coating, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 90 parts by weight of modified epoxy resin, 10 parts by weight of acrylic resin, 6 parts by weight of vinyl-terminated polydimethylsiloxane, 1 part by weight of hydrogenated silicone oil, 0.5 parts by weight of platinum catalyst, 0.8 parts by weight of Tween 80 emulsifier, 5 parts by weight of coconut shell activated carbon, 11 parts by weight of octadecyltriethoxysilane, 0.4 parts by weight of dibutyltin dilaurate, 8 parts by weight of isophoronediamine, 7 parts by weight of polydimethylsiloxane and 1 part by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:8, and adding 1-aminobenzotriazole; the addition amount of 1-aminobenzotriazole is 0.5% of the mass of bisphenol A epoxy resin; the addition amount of soft particles accounts for 5% of the total mass of the low ice adhesion coating; the addition amount of hard particles accounts for 3% of the total mass of the low ice adhesion coating; A magnetic stirrer is installed in a dry flask, and a condenser is installed. Dichloromethane is first added to the flask, and then bisphenol A epoxy resin is added. The amount of dichloromethane added is 30% of the mass of the epoxy resin. Stirring is started. After the epoxy resin is completely dissolved, o-trifluoromethylphenylethylamine is added. Stirring is continued. The reaction mixture is heated to 60° C. When the temperature is stable, 1-aminobenzotriazole is added. Stirring is maintained and the reaction is carried out at this temperature for 1 hour to obtain a modified epoxy resin. S1.2. Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, wherein the mass ratio of emulsifier to deionized water in the emulsion is 1:200, stir at 3000 rpm for 30 min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 60°C for 3 h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 2000 rpm for 5 min, then wash with deionized water and anhydrous ethanol for 3 times respectively, and finally dry at 80°C for 1 h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 18 hours, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution with a mass fraction of 2%, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder and the hydrophobic modifier in a mass ratio of 1:10, transfer to a three-necked flask after ultrasonic treatment for 60 minutes, stir and react in a water bath at 70°C for 8 hours, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 3 times respectively, and finally vacuum dry at 80°C for 18 hours to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300 rpm for 15 minutes at room temperature to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15 minutes, add isophorone diamine, continue ultrasonic treatment for 2-3 minutes, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 400 rpm for 10 minutes at room temperature, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3 minutes to obtain a low ice adhesion coating.
[0026] Embodiment 5: A method for preparing a soft-hard composite low ice adhesion anti-icing coating, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 75 parts by weight of modified epoxy resin, 25 parts by weight of acrylic resin, 8 parts by weight of vinyl-terminated polydimethylsiloxane, 3 parts by weight of hydrogenated silicone oil, 1 part by weight of platinum catalyst, 1.2 parts by weight of Tween 80 emulsifier, 10 parts by weight of coconut shell activated carbon, 13 parts by weight of octadecyltriethoxysilane, 0.8 parts by weight of dibutyltin dilaurate, 12 parts by weight of isophoronediamine, 9 parts by weight of polydimethylsiloxane and 3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:8, and adding 1-aminobenzotriazole; the addition amount of 1-aminobenzotriazole is 0.5% of the mass of bisphenol A epoxy resin; the addition amount of soft particles accounts for 5% of the total mass of the low ice adhesion coating; the addition amount of hard particles accounts for 3% of the total mass of the low ice adhesion coating; A magnetic stirrer is installed in a dry flask, and a condenser is installed. Dichloromethane is first added to the flask, and then bisphenol A epoxy resin is added. The amount of dichloromethane added is 30% of the mass of the epoxy resin. Stirring is started. After the epoxy resin is completely dissolved, o-trifluoromethylphenylethylamine is added. Stirring is continued. The reaction mixture is heated to 60° C. When the temperature is stable, 1-aminobenzotriazole is added. Stirring is maintained and the reaction is carried out at this temperature for 1 hour to obtain a modified epoxy resin. S1.2. Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, wherein the mass ratio of emulsifier to deionized water in the emulsion is 1:200, stir at 3000 rpm for 30 min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 60°C for 3 h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 2000 rpm for 5 min, then wash with deionized water and anhydrous ethanol for 3 times respectively, and finally dry at 80°C for 1 h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 18 hours, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution with a mass fraction of 2%, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder and the hydrophobic modifier in a mass ratio of 1:10, transfer to a three-necked flask after ultrasonic treatment for 60 minutes, stir and react in a water bath at 70°C for 8 hours, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 3 times respectively, and finally vacuum dry at 80°C for 18 hours to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300 rpm for 15 minutes at room temperature to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15 minutes, add isophorone diamine, continue ultrasonic treatment for 2-3 minutes, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 400 rpm for 10 minutes at room temperature, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3 minutes to obtain a low ice adhesion coating.
[0027] Embodiment 6: A method for preparing a soft-hard composite low ice adhesion anti-icing coating, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 85 parts by weight of modified epoxy resin, 25 parts by weight of acrylic resin, 8 parts by weight of vinyl-terminated polydimethylsiloxane, 3 parts by weight of hydrogenated silicone oil, 1 part by weight of platinum catalyst, 1.2 parts by weight of Tween 80 emulsifier, 10 parts by weight of coconut shell activated carbon, 13 parts by weight of octadecyltriethoxysilane, 0.8 parts by weight of dibutyltin dilaurate, 12 parts by weight of isophoronediamine, 9 parts by weight of polydimethylsiloxane and 3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:8, and adding 1-aminobenzotriazole; the addition amount of 1-aminobenzotriazole is 0.5% of the mass of bisphenol A epoxy resin; the addition amount of soft particles accounts for 5% of the total mass of the low ice adhesion coating; the addition amount of hard particles accounts for 3% of the total mass of the low ice adhesion coating; A magnetic stirrer is installed in a dry flask, and a condenser is installed. Dichloromethane is first added to the flask, and then bisphenol A epoxy resin is added. The amount of dichloromethane added is 30% of the mass of the epoxy resin. Stirring is started. After the epoxy resin is completely dissolved, o-trifluoromethylphenylethylamine is added. Stirring is continued. The reaction mixture is heated to 60° C. When the temperature is stable, 1-aminobenzotriazole is added. Stirring is maintained and the reaction is carried out at this temperature for 1 hour to obtain a modified epoxy resin. S1.2. Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, wherein the mass ratio of emulsifier to deionized water in the emulsion is 1:200, stir at 3000 rpm for 30 min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 60°C for 3 h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 2000 rpm for 5 min, then wash with deionized water and anhydrous ethanol for 3 times respectively, and finally dry at 80°C for 1 h to obtain silicone rubber microspheres, i.e. soft particles; S1.3, dry the coconut shell activated carbon in a vacuum drying oven at 100-120°C for 18 hours, then grind it through a 250 mesh sieve, take octadecyltriethoxysilane and dissolve it in anhydrous ethanol to prepare a silane solution with a mass fraction of 2%, and add dibutyltin dilaurate, mix and stir evenly to obtain a hydrophobic modifier, mix the ground coconut shell activated carbon powder and the hydrophobic modifier in a mass ratio of 1:10, transfer to a three-necked flask after ultrasonic treatment for 60 minutes, stir and react in a water bath at 70°C for 8 hours, cool and centrifuge after the reaction is completed, wash with anhydrous ethanol and deionized water for 3 times respectively, and finally vacuum dry at 80°C for 18 hours to obtain hard hydrophobic activated carbon particles, i.e. hard particles; S1.4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300 rpm for 15 minutes at room temperature to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15 minutes, add isophorone diamine, continue ultrasonic treatment for 2-3 minutes, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 400 rpm for 10 minutes at room temperature, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3 minutes to obtain a low ice adhesion coating.
[0028] Comparative Example 1: The method of Example 3 was adopted to directly use bisphenol A epoxy resin without modifying the bisphenol A epoxy resin by o-trifluoromethylphenethylamine and 1-aminobenzotriazole.
[0029] Comparative Example 2: The method of Example 3 was adopted, and bisphenol A epoxy resin and o-trifluoromethylphenethylamine were directly used without adding 1-aminobenzotriazole for modification.
[0030] The present invention adopts a modified epoxy resin to prepare a soft and hard composite low ice adhesion anti-icing coating, wherein the performance index inspection items and inspection standards of the soft and hard composite low ice adhesion anti-icing coating are as follows: According to the test method of ASTM D7334-08 (2022), the coating is applied to the substrate and the coating thickness is ensured to be uniform. The initial contact angle of the anti-icing coating is measured, and a drop of water is added to its surface. The freezing time of the water drop is recorded at -10°C to judge the anti-icing effect. The coating surface is tested by dragging the sample over 800-grit sandpaper under a load of 200g. The contact angle is tested 100 times with a linear movement of 10cm as a cycle. The wear resistance of the anti-icing coating is judged by the change in the contact angle after friction. The sample coated with the anti-icing coating is immersed in a hydrochloric acid solution with a pH of 1 and a sodium hydroxide solution with a pH of 13 for testing. After immersion for 170 hours, the corrosion of the sample is observed. According to GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test" standard tests the salt spray resistance of anti-icing coatings. Samples coated with low ice adhesion anti-icing coatings are placed in a salt spray chamber to evaluate the degree of rust. The neutral salt spray corrosion acceleration test is carried out in a salt spray corrosion test machine. The sample is placed on the plastic rack of the salt spray test chamber. The sample surface is 20° to the vertical direction. A 10wt% NaCl solution is used and the situation is observed after 120 hours. According to GB23987-2009 "Artificial weathering exposure of paint and varnish coatings to fluorescent ultraviolet light and water" standard, after the sample anti-icing coating is aged, its contact angle change is tested to determine its aging resistance.
[0031] According to the above standards, the soft-hard composite low ice adhesion anti-icing coatings prepared in the above Examples 1-6 and Comparative Examples 1-2 were tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-2 The above data fully demonstrates that compared with Comparative Examples 1-2, Examples 1-6 can fully demonstrate the role of modified epoxy resin in the anti-icing effect and durability of the soft-hard composite low ice adhesion anti-icing coating.
[0032] Since the present invention adopts modified epoxy resin to prepare the soft-hard composite low ice adhesion anti-icing coating, the anti-icing effect and durability of the soft-hard composite low ice adhesion anti-icing coating are effectively improved by the modified epoxy resin, as follows: It can be seen from Examples 1-3 that with the continuous increase in the proportion of the modified epoxy resin component, the anti-icing effect and durability of the anti-icing coating gradually increase. Since the trifluoromethyl group of trifluoromethylphenethylamine has a lower surface energy, the coating surface is more difficult to be wetted by water molecules. With the increase in the proportion of trifluoromethylphenethylamine, the hydrophobicity of the coating is further improved. 1-Aminobenzotriazole contains a basic functional group, which can accelerate the cross-linking reaction between the epoxy group and the curing agent to form a denser three-dimensional network structure, which not only enhances the mechanical strength and chemical resistance of the material, but also its ultraviolet absorption ability also improves the weather resistance and anti-aging properties of the coating.
[0033] It can be seen from Examples 3 and 4 that with the continuous changes in the content of other components, the anti-icing effect and durability of the anti-icing coating do not change significantly, which means that a small change in the content of other components within a certain range is not enough to cause a significant change in the anti-icing effect and durability of the anti-icing coating.
[0034] It can be seen from Examples 3, 5 and 6 that as the content of the modified epoxy resin continues to change, the anti-icing effect and durability of the anti-icing coating continue to change. When the content of the modified epoxy resin is gradually increased, on the one hand, it can produce more dense cross-linking points with the curing agent to form a stronger three-dimensional network structure. On the other hand, since the modified bisphenol A epoxy resin has good anti-icing effect and durability, the increase in its proportion also helps to improve the overall anti-icing effect and durability of the anti-icing coating.
[0035] According to the above test experiments, the soft-hard composite low ice adhesion anti-icing coating prepared according to Example 3 has the best performance, so Example 3 is taken as the best example; By comparing Example 3 with Comparative Examples 1-2, it can be seen that: Comparative Example 1 directly uses bisphenol A epoxy resin, and does not modify the bisphenol A epoxy resin by o-trifluoromethylphenethylamine and 1-aminobenzotriazole. The anti-icing effect and durability of the anti-icing coating are poor. The unmodified bisphenol A epoxy resin is more easily wetted by water than the modified epoxy resin, which increases the risk of icing. It does not contain 1-aminobenzotriazole with ultraviolet absorption ability, lacks effective protection against ultraviolet rays, and is prone to aging when exposed to the external environment for a long time, further weakening its protective effectiveness.
[0036] Comparative Example 2 directly uses bisphenol A epoxy resin and o-trifluoromethylphenethylamine without adding 1-aminobenzotriazole for modification. The anti-icing effect and durability of the anti-icing coating are poor. 1-Aminobenzotriazole can promote the reaction between bisphenol A epoxy resin and o-trifluoromethylphenethylamine to form a more stable three-dimensional network structure. However, due to the lack of ultraviolet protection function provided by 1-aminobenzotriazole, the coating is more susceptible to ultraviolet light, resulting in long-term performance degradation.
[0037] In summary, the epoxy resin modified with o-trifluoromethylphenethylamine and 1-aminobenzotriazole significantly improves the anti-icing effect and durability of the anti-icing coating. The trifluoromethyl group of o-trifluoromethylphenethylamine reduces the surface energy of the coating, enhances the hydrophobicity, and reduces the possibility of icing, while 1-aminobenzotriazole not only accelerates the curing reaction and forms a denser three-dimensional network structure, but also provides UV protection, enhances weather resistance and anti-aging properties. In addition, the introduction of a composite structure of hard and soft particles can not only effectively improve the mechanical properties of the material, but also form a local stress concentration area on the surface of the material, which helps to guide stress concentration when the ice layer is formed, promote local cracking and shedding of the ice layer, and accelerate the shedding process of ice, thereby improving the functionality and long-term stability of the anti-icing coating as a whole.
[0038] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a soft-hard composite low ice adhesion anti-icing coating, characterized in that: S1.1, weigh the following raw materials in parts by weight: 75-90 parts by weight of modified epoxy resin, 10-25 parts by weight of acrylic resin, 6-8 parts by weight of vinyl-terminated polydimethylsiloxane, 1-3 parts by weight of hydrogenated silicone oil, 0.5-1 parts by weight of platinum catalyst, 0.8-1.2 parts by weight of emulsifier, 5-10 parts by weight of coconut shell activated carbon, 11-13 parts by weight of octadecyltriethoxysilane, 0.4-0.8 parts by weight of dibutyltin dilaurate, 8-12 parts by weight of isophoronediamine, 7-9 parts by weight of polydimethylsiloxane and 1-3 parts by weight of aliphatic polyisocyanate; The modified epoxy resin is prepared by mixing bisphenol A epoxy resin and o-trifluoromethylphenylethylamine in a mass ratio of 50:6-8, and adding 1-aminobenzotriazole; S1.2, preparing silicone rubber microspheres, i.e. soft particles, from vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil, platinum catalyst, emulsifier and deionized water; S1.3, preparing hard hydrophobic activated carbon particles, i.e. hard particles, from coconut shell activated carbon, octadecyltriethoxysilane, anhydrous ethanol and dibutyltin dilaurate; S1.
4. Place acrylic resin and modified epoxy resin in a beaker, then add soft particles and hard particles to the beaker containing the mixed resin, and stir with a magnetic stirring bar at a constant speed of 300-400rpm at room temperature for 15-20min to ensure that the mixture is evenly blended, then ultrasonically treat the mixture for 15-20min, add isophorone diamine, continue ultrasonic treatment for 2-3min, stop ultrasonic treatment, add polydimethylsiloxane, stir with a magnetic stirring bar at 300-400rpm at room temperature for 10-15min, finally add aliphatic polyisocyanate, and continue stirring the mixture for 3-5min to obtain a low ice adhesion coating.
2. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 1, characterized in that: The specific steps involved in S1.2 are: Add vinyl-terminated polydimethylsiloxane, hydrogenated silicone oil and platinum catalyst into a constant temperature reactor, add emulsifier and deionized water into another beaker, stir at 2000-3000rpm for 20-30min to form an emulsion, transfer the emulsion to a constant temperature reactor, react at 50-60℃ for 2-3h, stir continuously during the reaction, after the reaction is completed, cool the mixture naturally, centrifuge at 1000-2000rpm for 3-5min, then wash with deionized water and anhydrous ethanol for 2-3 times respectively, and finally dry at 70-80℃ for 1-2h to obtain silicone rubber microspheres, i.e. soft particles.
3. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 2, characterized in that: In the S1.2, the mass ratio of the emulsifier to the deionized water in the emulsion is 1:100-200, and the particle size range of the silicone rubber microspheres is 3-7 μm.
4. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 1, characterized in that: The specific steps involved in S1.3 are: The coconut shell activated carbon is dried in a vacuum drying oven at 100-120°C for 12-18h, then ground through a 250 mesh sieve, octadecyltriethoxysilane is dissolved in anhydrous ethanol to prepare a silane solution, and dibutyltin dilaurate is added, mixed and stirred evenly to obtain a hydrophobic modifier, the ground coconut shell activated carbon powder is mixed with the hydrophobic modifier, and after ultrasonic treatment for 50-60min, it is transferred to a three-necked flask, stirred and reacted in a water bath at 60-70°C for 6-8h, cooled and centrifuged after the reaction is completed, washed with anhydrous ethanol and deionized water for 2-3 times respectively, and finally vacuum dried at 60-80°C for 12-18h to obtain hard hydrophobic activated carbon particles, i.e. hard particles.
5. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 4, characterized in that: In the S1.3, the mass fraction of the silane solution is 1-3%, and the mass ratio of the ground coconut shell activated carbon powder to the hydrophobic modifier is 1:10-15.
6. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 1, characterized in that: In S1.4, the amount of soft particles added is 1-10% of the total mass of the low ice adhesion coating.
7. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 1, characterized in that: In the S1.4, the amount of hard particles added is 1-8% of the total mass of the low ice adhesion coating.
8. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 1, characterized in that: In S1.4, the steps of preparing the modified epoxy resin are specifically as follows: Assemble a magnetic stirrer in a dry flask and install a condenser. First add dichloromethane into the flask, then add bisphenol A epoxy resin, start stirring, and after the epoxy resin is completely dissolved, add trifluoromethylphenethylamine and continue stirring. Heat the reaction mixture to 50-60°C. When the temperature stabilizes, add 1-aminobenzotriazole, keep stirring and react at this temperature for 1-2 hours to obtain a modified epoxy resin.
9. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 8, characterized in that: The added amount of the 1-aminobenzotriazole is 0.1-0.5% of the mass of the bisphenol A epoxy resin.
10. The method for preparing the soft-hard composite low ice adhesion anti-icing coating according to claim 8, characterized in that: The added amount of the dichloromethane is 20-30% of the mass of the epoxy resin.
Citation Information
Patent Citations
Core-shell particle for toughening thermosetting resin, composite material and preparation method
CN116478536A
Durable superhydrophobic coating
US20070009657A1
Cited By
Adhesive for powder injection molding process as well as preparation method and application of adhesive
CN120438605A
A binder for powder injection molding process and its preparation method and application
CN120438605B